2014
DOI: 10.1037/a0037245
|View full text |Cite
|
Sign up to set email alerts
|

Moral character in the workplace.

Abstract: Using two 3-month diary studies and a large cross-sectional survey, we identified distinguishing features of adults with low versus high levels of moral character. Adults with high levels of moral character tend to: consider the needs and interests of others and how their actions affect other people (e.g., they have high levels of Honesty-Humility, empathic concern, guilt proneness); regulate their behavior effectively, specifically with reference to behaviors that have positive short-term consequences but neg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
199
2
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 263 publications
(208 citation statements)
references
References 106 publications
(245 reference statements)
5
199
2
2
Order By: Relevance
“…Moral Integrity was not related to Loyalty or Respect for Authority. These results are consistent with those reported by Cohen, Panter, Turan, Morse, and Kim (2014) in a study of moral character in the workplace. Cohen and colleagues found that whereas the moral foundations of Harm and Fairness, and the IRI empathy and perspective-taking subscales, were relevant to moral character (which predicted moral behavior), Loyalty, Respect for Authority, and Purity were not.…”
Section: Discussion Studysupporting
confidence: 95%
“…Moral Integrity was not related to Loyalty or Respect for Authority. These results are consistent with those reported by Cohen, Panter, Turan, Morse, and Kim (2014) in a study of moral character in the workplace. Cohen and colleagues found that whereas the moral foundations of Harm and Fairness, and the IRI empathy and perspective-taking subscales, were relevant to moral character (which predicted moral behavior), Loyalty, Respect for Authority, and Purity were not.…”
Section: Discussion Studysupporting
confidence: 95%
“…We were interested in the question of which scale conceptualization performs best, particularly in these settings, since a growing body of studies uses the BSCS to investigate the role of TSC at school (Duckworth & Seligman, 2005), in university (Tangney et al, 2004), in vocational training (e.g., Baay et al, 2014), and in the company (e.g., Cohen, Panter, Turan, Morse, & Kim, 2014). To this end, we used confirmatory factor analysis (CFA) to compare the factor structure of the different models and the usefulness of the facet scores with the total score in predicting educational and job-related outcomes hypothesized to be related to TSC.…”
Section: The Present Researchmentioning
confidence: 99%
“…Nevertheless, future research can examine how attachment orientation and emotional exhaustion are related to more objective measures of performance and ethical behavior, like supervisor ratings (Simmons et al, 2009). Future research can examine other individual difference constructs and broaden the number of mediators in explaining unethical workplace behavior across different cultural and stressful contexts (Cohen, Panter, Turan, Morse, & Kim, 2014). These limitations notwithstanding, the associations between attachment orientation and workplace decision-making found in the current studies highlight the utility of examining organizational issues through a relational lens.…”
Section: Discussionmentioning
confidence: 87%